2012
DOI: 10.1007/978-3-642-31594-7_55
|View full text |Cite
|
Sign up to set email alerts
|

Converting Online Algorithms to Local Computation Algorithms

Abstract: Abstract. We propose a general method for converting online algorithms to local computation algorithms, 3 by selecting a random permutation of the input, and simulating running the online algorithm. We bound the number of steps of the algorithm using a query tree, which models the dependencies between queries. We improve previous analyses of query trees on graphs of bounded degree, and extend this improved analysis to the cases where the degrees are distributed binomially, and to a special case of bipartite gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(73 citation statements)
references
References 19 publications
1
72
0
Order By: Relevance
“…[MRVX12], showed that it is possible to transform any on-line algorithm on a graph of bounded degree (or whose degree is distributed binomially) to an LCA. The idea behind the reduction is simple: generate a random permutation on the vertices and simulate the on-line algorithm on this permutation.…”
Section: Theorem 62 [Mye81 At01]) the Allocation Algorithm A Admitmentioning
confidence: 99%
See 4 more Smart Citations
“…[MRVX12], showed that it is possible to transform any on-line algorithm on a graph of bounded degree (or whose degree is distributed binomially) to an LCA. The idea behind the reduction is simple: generate a random permutation on the vertices and simulate the on-line algorithm on this permutation.…”
Section: Theorem 62 [Mye81 At01]) the Allocation Algorithm A Admitmentioning
confidence: 99%
“…They show that, with high probability, this results in at most O(log n) queries. We require the following theorem from [MRVX12]. …”
Section: Theorem 62 [Mye81 At01]) the Allocation Algorithm A Admitmentioning
confidence: 99%
See 3 more Smart Citations